2019
DOI: 10.1177/1354068818819243
|View full text |Cite
|
Sign up to set email alerts
|

Social and ideological representativeness: A comparison of political party members and supporters in Finland after the realignment of major parties

Abstract: This study provides a new frame of reference for understanding intraparty dynamics by analyzing party members’ representativeness with respect to party supporters regarding socioeconomic status and the ideological spectrum in a multiparty system, namely that of Finland. The analysis is based on a unique member-based survey of Finland’s six major political parties ( N = 12,427), which is combined with supporter data derived from a nationally representative survey ( N = 1648). The clearest difference was found b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…In Finland, the main division has been drawn between the supporters of the populist right-wing party, the Finns, and the supporters of the Green League and the Left Alliance (Koiranen et al, 2020). However, it is noteworthy that Finland has a multiparty system based on socioeconomic cleavages represented by traditional parties, such as the Social Democratic Party of Finland, the National Coalition Party, and the Center Party (Koivula et al, 2020). Indeed, previous research has shown that there is relatively little affective polarization in Finland (Wagner, 2021).…”
Section: Target Attractivenessmentioning
confidence: 99%
“…In Finland, the main division has been drawn between the supporters of the populist right-wing party, the Finns, and the supporters of the Green League and the Left Alliance (Koiranen et al, 2020). However, it is noteworthy that Finland has a multiparty system based on socioeconomic cleavages represented by traditional parties, such as the Social Democratic Party of Finland, the National Coalition Party, and the Center Party (Koivula et al, 2020). Indeed, previous research has shown that there is relatively little affective polarization in Finland (Wagner, 2021).…”
Section: Target Attractivenessmentioning
confidence: 99%
“…As these new identity parties, the FP and the GL, have diverged from the traditional left-right spectrum, the Left Alliance (LA) has also actively developed from a traditional working-class party into a so-called new left party. Nowadays the LA is-alongside with the GL-firmly based on shared post-materialist values and opinions concerning, for example, equality, tolerance, and minority rights, especially in terms of gender, ethnicity, and sexuality (Koivula et al, 2019;Lönnqvist et al 2019). This transformation can also be detected in the changed background of the party's members and supporters: the LA's new members and supporters in this decade are more likely to be highly educated, young, and female (Keipi et al, 2017).…”
Section: Party Preference and Political Values In The Finnish Online Public Spherementioning
confidence: 99%
“…Regarding both refugee attitudes and attitudes towards the environment, the Finns Party and the Greens are polar opposites (Koivula, Koiranen, Saarinen, & Keipi, 2019). Almost 90% of the members of the Finns Party view refugees as an important societal risk, whereas above 60% of Green League members do not view refugees as an important risk.…”
Section: Polarization In Finlandmentioning
confidence: 99%